2020
DOI: 10.3892/etm.2020.8878
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑654‑3p enhances cisplatin sensitivity by targeting QPRT and inhibiting the PI3K/AKT signaling pathway in ovarian cancer cells

Abstract: Dysregulation of microRNAs serves a crucial role in the chemosensitivity to cisplatin (DDP) in ovarian cancer (OVC). The abnormal expression of microRNA (miR)-654-3p has been reported in several types of human cancer. However, the association between miR-654-3p and cisplatin resistance in human OVC remains unclear. The present study aimed to investigate the role and mechanism of miR-654-3p in DDP resistance in OVC. The results demonstrated that miR-654-3p was significantly downregulated in ovarian cancer tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…miR-654-3p is downregulated in ovarian cancer ( 47 ), gastric cancer ( 48 ) and papillary thyroid cancer ( 49 ), but is upregulated in osteosarcoma ( 50 ). Moreover, miR-654-3p exerts cancer-inhibiting ( 47 49 ) or cancer-promoting roles ( 50 ), and is implicated in cancer oncogenesis and progression ( 47 50 ). A recent study reported that miR-654-3p expression was down-regulated in HCC, which was associated with poor patient prognosis, and that overexpression of miR-654-3p restricted cell proliferation, migration and invasion in HCC ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-654-3p is downregulated in ovarian cancer ( 47 ), gastric cancer ( 48 ) and papillary thyroid cancer ( 49 ), but is upregulated in osteosarcoma ( 50 ). Moreover, miR-654-3p exerts cancer-inhibiting ( 47 49 ) or cancer-promoting roles ( 50 ), and is implicated in cancer oncogenesis and progression ( 47 50 ). A recent study reported that miR-654-3p expression was down-regulated in HCC, which was associated with poor patient prognosis, and that overexpression of miR-654-3p restricted cell proliferation, migration and invasion in HCC ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are non-coding RNAs that are ~22 nt in length and play key regulatory roles in the development and chemoresistance of human cancers (14). For example, Niu et al (15) revealed that miRNA-654-3p enhanced cisplatin (DDP) sensitivity by downregulating quinolinate phosphoribosyl transferase and suppressing the PI3K/AKT pathway in ovarian cancer. Yang et al (16) suggested that miRNA-181a-5p promoted the sensitivity of esophageal adenocarcinoma cells to DDP by targeting Cbl proto-oncogene B.…”
Section: Introductionmentioning
confidence: 99%
“…Acquired cisplatin resistance is a serious problem for the therapy of OC patients ( 8 , 24 ). miRNAs actually participated in the regulation of tumorigenesis and drug resistance in OC ( 11 , 25 ). By quantified the expression of miR-4461 in cisplatin-resistant cell lines, we found that miR-4461 expression was enhanced in resistant cells, suggesting that high expression of miR-4461 might be associated with cisplatin resistance in OC.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, increasingly evidence has emerged to emphasize that the function of miRNAs in cisplatin resistance in human cancers. For instance, the sensitivity on the cisplatin of miR-654-3p is enhanced by targeting QPRT and the PI3K/AKT signaling pathway in OC cells is suppressed ( 11 ). MiR-186 achieved the regulation of cisplatin sensitivity on ovarian cancer cells in two directions simultaneously, which not only inhibiting PIK3R3 and PTEN, but also promoting expression of APAF1 as well ( 12 ).…”
Section: Introductionmentioning
confidence: 99%